Purslane oleracea polysaccharides alleviate male reproductive damage caused by acrylonitrile by improving gut microbiota dysbiosis and metabolic disorder - Weihua Li; Hongbing Li; Jing Wu; Chenggang Jia; Yanli Lei (Scientific Reports)
Abstract Acrylonitrile (ACN), a prevalent environmental pollutant, is associated with disruptions in male reproductive health. Recently, Portulaca oleracea polysaccharide (POP) has garnered considerable attention for its ability to modulate gut microbiota and demonstrate antioxidative properties. However, its the mechanisms of reproductive damage remain poorly understood. To investigate POP’s protective effects against ACN-induced reproductive damage, we orally gavaged ACN to male mice (26 mg/kg) to induce reproductive toxicity, then intervened with POP (200 mg/kg). This study assessed the impact of ACN exposure and evaluated POP intervention on gut microbiota, Metabolic Profiles, and reproductive function. We performed 16S rRNA gene amplicon sequencing of fecal samples (n = 6 ACN, POP and healthy controls) and untargeted metabolomic profiling using LC–MS analysis in mice exposed to ACN and treated with POP. Compared with controls, ACN exposure induced significant gut microbiota dysbiosis, characterized by altered relative abundances of specific genera, including Lactobacillus, recombinant Escherichia coli HT002, Alloprevotella, Rikenella, Clostridia_UCG-014, Turicibacter, and Lactococcus. These changes were accompanied by metabolic disturbances, including a significant decrease in the metabolite 2-aminopropenoic acid (VIP > 1, p < 0.05 and fold change (FC) > 1.2), which was significantly increased following POP intervention (p < 0.05). Furthermore, POP alleviated ACN-induced testicular tissue damage, oxidative stress, disruption in glucose-lipid and energy metabolism, and improved the sperm capacitation rate. Integrative analyses revealed a strong association between gut microbiota imbalance, metabolic alterations, and reproductive dysfunction, highlighting the protective role of POP in mitigating ACN-induced adverse effects. These findings demonstrate that POP protects reproductive health by mitigating toxin-induced damage and potentially enhancing reproductive function under environmental and metabolic stress. It also holds promise for functional food and drug development.